845 The practical experience for diphoterine® solution in dealing with chemical burns. (24th April 2018) - Mathieu, Laurence; Hsu-Hua, Lin; Li-Mei, Liu; Jiin-Chyuan, Luo; Hall, Alan H
Abstract : Introduction: Chemical burns represent about 10% of all burns. About 70% of chemical burns are caused by chemical substances used in industrial production, showing the importance of prevention. Water, easily available is often used as emergency management at workplace, and pre-hospital first aid measures. Evidently, the earlier the product is rinsed, better the efficacy, but is the traditional approach the best measure nowadays? Methods: This paper demonstrates shared management experience in treating chemical burn incident at a petrochemical plant in Taiwan on corrosive and toxic agents such as sulfuric acid, maleic acid, acetic acid, ammonia, sodium hypochlorite, caustic soda and pure and diluted phenol. Chemical simulation ( in vitro ) and live animal test ( in vivo ) showed that Diphoterine solution can effectively decontaminate 600 kinds of chemical substances, including acids, alkali, oxidants and reducing agents, irritants, tear gas, solvents and alkyl compounds. It can be used as an emergency shower device in factories, emergency devices in factory health centres, clinics and hospital ambulances, decontamination equipment for toxic poisoning systems, CBRN Disaster Prevention and Relief systems while part of Medical Device in European hospitals. Currently this product is positioned as an emergency decontamination solution for chemical splashing, and as emergency decontamination solution in the case of CBRN in Taiwan. Results: We have a better understanding of using Diphoterine solution regarding acid and alkali burns management at workplace before hospitalisation. Acid or alkali splashing incidents can be heard of from time to time, and even happened in emergency department. Conclusion: Perhaps, it is now time to use Diphoterine, an aqueous decontamination solution with high reverse osmosis for decontaminating eyes and skin splashed by chemical substances as treatment in emergency.